(untitled) (PIONIR: JURNAL PENDIDIKAN, 2020)
In learning activities the teacher should have a sufficiently mature teaching plan. Teaching planning is closely related to various elements such as teaching objectives, teaching materials, learning activities, teaching methods and evaluation. These elements are an integral part of the overall responsibility of the teacher in the learning process. The role and function of teachers is one of the most important teacher qualifications. If creativity and competence are not present in a teacher, he will not be competent in doing his job and the results will not be optimal. With their creativity and competence, apart from mastering the material and being able to process teaching and learning programs, teachers are also required to be able to carry out evaluation and administration. The ability of teachers to develop the learning process and their mastery of teaching materials is not sufficient. The teacher’s ability to master the class is balanced with the ability to evaluate student competency planning which is very decisive in the context of subsequent planning, or the treatment policy for students related to the concept of complete learning, therefore the function and role of the teacher in planning and implementing the learning process is a major factor. in achieving learning objectives. The skills to plan and implement this learning process are closely related to the duties and responsibilities of the teacher as an educating teacher. Teachers as educators have a very broad meaning, not just providing teaching materials, but reaching out to ethical and aesthetic behavior in facing the challenges of life in society.